2020
DOI: 10.2196/14073
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention Delivered by Mobile Phone Instant Messaging to Increase Acceptability and Use of Effective Contraception Among Young Women in Bolivia: Randomized Controlled Trial

Abstract: Background Although the most effective methods of contraception are available in Bolivia, unmet need for contraception among women aged 15 to 19 years is estimated to be 38% (2008), and the adolescent fertility rate is 71 per 1000 women (2016). Mobile phones are a popular mode to deliver health behavior support. We developed a contraceptive behavioral intervention for young Bolivian women delivered by mobile phone and guided by behavioral science. The intervention consists of short instant messages… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…In family planning specifically, a number of published studies evaluate the effects of short message service (SMS) or rapid message interventions, but report only effects on variables such as contraceptive knowledge or attitudes. These evaluations do not measure or do not find any evidence of shifts in behaviours such as contraceptive use 16–20. Accordingly, a broader evidence base is needed 21…”
Section: Introductionmentioning
confidence: 99%
“…In family planning specifically, a number of published studies evaluate the effects of short message service (SMS) or rapid message interventions, but report only effects on variables such as contraceptive knowledge or attitudes. These evaluations do not measure or do not find any evidence of shifts in behaviours such as contraceptive use 16–20. Accordingly, a broader evidence base is needed 21…”
Section: Introductionmentioning
confidence: 99%
“…McCarthy et al implemented a mHealth intervention including a mobile app with standard family planning information and intervention messages in two countries i.e., Bolivia and Palestine. The intervention in both countries did not find any difference in the uptake of contraception, whereas, in Palestine, participants reported at least one method of contraceptive acceptable (adjusted OR 2.34; 95% CI 1.48–3.68) ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 85%
“…Mobile health or mHealth intervention such as short message services (SMS), and mobile app are also identified as effective tools to increase SRH knowledge of adolescent girls ( 27 , 28 , 30 , 33 , 35 , 36 , 49 , 59 ), studies reported that mHealth interventions have the potential to engage and increase SRH knowledge of adolescent girls who are at higher risk of poor SRH outcomes, including adolescents with low parental education and support, adolescents with low SRH knowledge, and adolescents with an early sexual debut ( 27 , 28 , 30 , 33 , 35 , 36 , 58 ). Njuguna et al reported that the use of weekly text messages about HIV prevention and reproductive health significantly increased rates of HIV testing among young girls in Kenya ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, we may have seen no difference between the arms because the intervention was truly not better than SMS-prompted self-learning and/or no intervention at all. Several other RCTs that have attempted to tie adolescent-targeted digital health interventions to SRH knowledge, acceptability or behavioural outcomes have resulted in similarly inconclusive findings,26 37–40 indicating that digital interventions on their own may not be enough to encourage behavioural change. However, while the above reasons would explain the lack of difference between arms, they do not explain why participants in all arms believed significantly fewer myths at endline than they did at baseline.…”
Section: Discussionmentioning
confidence: 99%